Does the Protection of River Basin Ecosystems Produce Broken Window Effect? Evidence From Spatial Choice Experiment in Xijiang River Basin, China - Nie, Xin; Chen, Zhoupeng; Yang, Linfang; Qing, Yiting; Wang, Han (Frontiers in Marine Science, 2022)
Eco-environmental protection of river basins and compensation for damages have been important issues for researchers around the world for a long time. Many studies have focused on the correlations among individual socioeconomic characteristics, ecological cognition, and differences in the willingness to pay. However, no research has been conducted from the perspective of perceived environmental quality. According to the Broken Windows Theory, the public’s willingness and behaviors regarding environmental protection are determined largely by earlier perceptions of environmental quality. Therefore, we used a spatial choice experiment to investigate the willingness of the public to pay for ecosystem restoration in the upper, middle, and lower reaches of the Xijiang River Basin in China. This paper discusses if perceived environmental quality is a factor that creates different levels in the willingness to pay. Our results show that the Broken Window Effect can better explain these differences. Living in a better ecological environment, the upper-reaches public expect to pay for the restoration of the river basin’s ecosystem to a higher state and is willing to be the “first person” to repair the “broken windows”, whereas those in the middle and lower reaches are willing to pay only for a restoration to a good state.